A History of Competitive Gaming - Lu, Zhouxiang, author.
1 online resource.
Keywords: "Competitive gaming, or esports - referring to competitive tournaments of video games among both casual gamers and professional players - began in the early 1970s with small competitions like the one held at Stanford University in October 1972, where some 20 researchers and students attended. By 2022 the estimated revenue of the global esports industry is in excess of $947 million, with over 200 million viewers worldwide. Regardless of views held about competitive gaming, esports have become a modern economic and cultural phenomenon. This book studies the full history of competitive gaming from the 1970s to the 2010s against the background of the arrival of the electronic and computer age. It investigates how competitive gaming has grown into a new form of entertainment, a sport-like competition, a lucrative business and a unique cultural sensation. It also explores the role of competitive gaming in the development of the video game industry, making a distinctive contribution to our knowledge and understanding of the history of video games. A History of Competitive Gaming will appeal to all those interested in the business and culture of gaming, as well as those studying modern technological culture"--